Photochemical synthesis of dihydroquinolinones and their investigation toward macrocycle synthesis via ring expansion - Magura, Chipo (Department of Chemistry, 2024)
There are several macrocyclic drugs that are currently on the market. As representative examples, erythromycin and azithromycin are currently approved antibiotics. Macrocycles are also used to treat other infectious diseases, for example, natamycin and amphotericin B are used as antifungal agents and ivermectin is used as an antiparasitic agent.1 The synthesis of macrocyclic compounds is typically done using an end-to-end macrocyclization approach. However, challenges arise due to competing intermolecular reactions leading to the use of high dilution conditions. It is therefore important that synthetic chemists develop general and modular methods for their synthesis in order to produce the next generation of therapeutic macrocyclic drugs. One such method is the Successive Ring Expansion (SuRE) protocol developed by Unsworth and co-workers at the University of York, offering an innovative and straightforward way to access such compounds. With this methodology, a cyclic starting material such as a lactam, is coupled to a N-protected β-amino acid fragment which is then deprotected to yield the ring-expanded cyclic product following rearrangement. Given our group's interest in the development of dihydroquinolinones (DHQs) and realizing that their suitability for SuRE had not yet been investigated, we recognised an opportunity to collaborate with the Unsworth group, as it would enable the synthesis of more diversely functionalised macrocyclic molecules. Visible-light mediated triplet energy transfer has enabled the synthesis of N-substituted DHQs by our group and others through a formal C(sp2)-H/C(sp3)-H hydroarylation.2–5 However, none of these methods have reported such syntheses producing the N-unsubstituted DHQ — which is required for the SuRE. Thus we first set out to optimise this photochemical cyclisation to enable the direct formation of Nunsubstituted DHQs. Gratifyingly, this reaction was successfully developed, requiring the use of an iridium photocatalyst, and was able to provide a diverse range of unprotected DHQs that could be investigated in the SuRE In application towards the synthesis of macrocycles using the SuRE methodology, a model DHQ was first investigated. Unfortunately, in the event, the N-unsubstituted DHQ was obtained instead of the ring-expanded product.After facing this challenge, Conjugate Addition or Ring Expansion (CARE) method, also developed by the Unsworth and coworkers was considered6, however the acylation to generate the key starting material was unsuccessful. To overcome the acylation, and in a third strategy (returning to a SuRE approach), we thought to replace the amide linker with an alkyl chain instead and effect a SuRE macrocyclization following a Staudinger deprotection in the presence of triphenylphosphine. The intermediate was successfully synthesised, and while a trial reaction revealed promising results, this is still under investigation. Analysis of the product mixture by NMR suggested the desired product formation, however residual triphenylphosphine oxide (TPPO) complicated this analysis. Time constraints prevented further investigation, however methods to remove or avoid the formation of TPPO will be a topic of future work. Since our direct DHQ synthesis requires an expensive iridium photocatalyst, we considered a demethylation strategy for the synthesis of N-unsubstituted DHQs from N-methyl DHQs — as these can be accessed using inexpensive thioxanthone photosensitisers.3 A related demethylation of amides was reported by Yi et al using a Cu catalyst and NFSI as an oxidant7 and in our attempt to use this procedure to produce the unprotected DHQ, we obtained the unsaturated quinolinone, instead. Quinolinones are important biological molecules and are used as antiviral, anticancer, antiulcer, and antihistaminic agents in medicinal chemistry, and thus we were very pleased with this result. These relatively mild oxidation conditions also offer opportunities for late-stage functionalization.8 Ultimately, through the use of photocatalysis, we could develop this oxidation chemistry to avoid the need for a metal — favouring a thioxanthone photosensitiser over a copper catalyst, and the reaction could be conducted at ambient temperature, rather than at 80 oC as per Yi et al's conditions. This methodology is of great importance because existing methods for this transformation make use of expensive transition metals such as Pd8–10 and Pt11 or require even higher temperatures.12